Methodology of professional self-reflection development (on the example of management activity) - A. Chupina, Valentina; A. Fedorenko, Olga; Yu. Pleshakova, Anastasia (International Journal of Engineering and Technology, 2018)
The effectiveness of management personnel, their ability to professional communication at the level of self-organization, their analytical and predictive abilities are determined by culturally organized self-reflection which promotes the realization and development of the innovative potential of the individual. The aim of the research is to theoretically substantiate reflexive self-organization in managerial activities, to develop and implement a professional module on the reflexive thinking of management personnel, and to identify effective methods for the development of professional reflection. The general scientific (analysis, synthesis, generalization, formalization and language schematization) and specific-scientific (observation, comparative analysis, questionnaires, tests) methods were used. They allowed obtaining an integral picture of the influence of reflection on the success of professional and social activity and creating conditions for the further development of reflection, personal qualities and the formation of an emotional and value-related attitude towards the activity. The article defines the essential features and functions of reflection, reveals the content of the reflexive method, establishes the links between the elements of reflection (analysis, criticism, standardization) and traditional types of managerial activity: goal-setting, support, correction and control of activity, and describes levels of reflexive thinking in managerial activities. The theoretical substantiation of the problem of reflexive self-organization and its solution in the course of realization of the professional module in undergraduates of the field â€˜State and municipal managementâ€™ is presented in the paper. Practical significance lies in creating a professional module aimed at developing reflection and implemented in the form of organizational and activity game, as well as diagnostic techniques for measuring the level of reflection.Â